EFFECT OF BRAKE THERMAL STRESS ON UNIAXIAL FATIGUE OF RAILWAY WHEEL PLATE - HUANG XiaoQing; SHEN XiaoHui; ZHANG Lei; XIAO Feng (Jixie qiangdu)
With development of heavy load train,the thermomechanical fatigue is the main failure form of wheel plate. The thermal stress was analysisbased on ANSYS softwarein this thesis. Uniaxial fatigue criterion and fatigue limit diagram of HaighGoodman was used to evaluate wheel plate fatigue. The effect of thermal stress on uniaxial fatigue of wheel plate was analysis. The result show that（ 1） Without consider brake thermal stresses,the fatigue resistance of each node of the new and worn wheel are satisfactory,and the manufactured stresses cause the fatigue weak position to transfer. The sections most prone to fatigue are located in 0 °、180 °and 40° ～ 60 °.（ 2） Considering brake thermal stresses,the fatigue resistance of each node of the new and worn wheel are satisfactory. Nevertheless,the mean stress of FPH and BPR not meet safety requirements.